Small-island interactions: pottery from Roman Malta - Anastasi, M (2015)
This thesis is an investigation of Roman pottery from the Maltese islands from the 1st century BC to the mid-4th century AD, and how pottery can help assess Malta's economic role in the wider central Mediterranean region. The archipelago’s locally produced vessels, its range of ceramic exports, and the quantification of the types of amphorae, fine, and cooking wares the islands imported, were studied and the data were used to compare with the pottery available from the small islands of Pantelleria, Lampedusa and the Kerkennah isles. The aim is to revisit the theme of the economic role of the Maltese islands and other similar-sized islands in the region by moving away from the tradition of unilateral and monographic narratives, which more often than not, omit the wealth of information that can be garnered from pottery. In the first instance, a detailed study of three complete and new ceramic assemblages, including amphorae, fine, cooking and coarse wares, was undertaken. The opportunity to quantify identifiable imports and compare them with local products—the first of its kind for fine, cooking and coarse wares—provided valuable proxy data for comparing Malta with neighbouring islands and centres, and demonstrated what proportion of ceramic vessels were locally supplied, and how these changed over time. These data were also fed into a series of network analyses, which plotted the common pottery links shared between small-island and mainland sites in the region. The analyses were interpreted in conjunction with a critique of existing pottery quantification methods, and the potential acceptance for utilising all known pottery data irrespective of the quality and quantity of the published data available. Most importantly, the import trends obtained from this study were incorporated into the existing narrative of how small islands and their local industries featured in the central Mediterranean’s regional economy, highlighting the types of archaeologically visible industries that existed; how these developed symbiotically alongside other larger supply networks; and what effect this might have had on the integration of small islands in the Roman Mediterranean.